Meningkatkan Keaktifan Siswa Kelas IX Pada Mata Pelajaran Fiqih Melalui Metode Resitasi di MTs Al Jam'iyatul Washliyah Selesai - Melli Nia; Hemawati Hemawati; San Putra (Departement of Mathematics Education, 2024)
Quality education is really needed by a nation to achieve the educational goals that have been set. Teachers as the main actors in the world of education really determine the quality of learning in schools. The reform era demands a Student Center Learning (SCL) learning pattern , where students are required to be more active and effective in participating in learning. Good quality teachers will be able to choose the right methods so that active student learning can be achieved. One of them is the application of the recitation method which is believed to increase students' active learning at school. The aim of this research is to increase students' active learning in Fiqh subjects in class IX. The method used in this research is classroom action research, by conducting two tests in cycle I and cycle II until satisfactory results. The data collection technique used in this research is observation technique. The results of this research are that the recitation method is proven to be able to increase students' active learning in the Fiqh class IX subject at MTS Al Jam'iyatul Washliyah Completed by 26.19%. From 69.64% in cycle I to 95.83% in cycle II.